Probing the Role of Backbone Hydrogen Bonding in a Critical β-sheet of the Extracellular Domain of a Cys-loop Receptor - Gleitsman, Kristin R. (2009)
Long-range communication is essential for the function of members of the Cys-loop family of neurotransmitter-gated ion channels. The involvement of the peptide backbone in binding-induced conformational changes that lead to channel gating in these membrane proteins is an interesting, but unresolved issue. To probe the role of the peptide backbone, we have incorporated a series of α-hydroxy acid analogues into the β-sheet rich extracellular domain of the muscle subtype of the nicotinic acetylcholine receptor, the prototypical Cys-loop receptor. Specifically, mutations were made in β-strands 7 and 10 of the α-subunit. A number of single backbone mutations in this region were well-tolerated. However, simultaneous introduction of two proximal backbone mutations led to surface-expressed, non-functional receptors. Together, these data suggest that while the receptor is remarkably robust in its ability to tolerate single amide-to-ester mutations throughout these β-strands, more substantial perturbations to this region have a profound effect on the protein. These results support a model in which backbone movements in the outer β-sheet are important for receptor function.